O processo de criação e implementação de unidades de conservação e sua influência na gestão local: o estudo de caso da área de proteção ambiental da ilha do Combu, em Belém/PA - CIRILO, Brenda Batista (Universidade Federal do Pará, 2013)
This is a case study which seeks to analyze the creation process of the Environmental Protection Area (APA) Combu Island, a state sustainable use conservation unit, located in the Amazon estuary, in the insular region of Belém, State of Pará. The study aimed to demonstrate that some aspects of the creation process of the APA Combu Island prevent its management from being consolidated. To contextualize the area, the results of a survey conducted by the manager of the unit, in 2010, with the heads of 100 households, distributed among the four communities in the island, are available. In 2013, a field survey was conducted with the same people, to ascertain their level of knowledge about the creation process of the APA. Ten people related to the process of creation, deployment and management of the unit were also interviewed for further information on the topic and to confront or validate the results of the field research. Since this is a qualitative study, we also analyzed: a) the unit planning and management; b) the historical trajectory of national conservation policy, c) the historical trajectory of conservation policy in the Amazon region and in the State of Pará. The results obtained through the field research show that: the creation of APA Combu Island was result of an indication from scientific studies conducted by Emilio Goeldi Museum of Pará (MPEG) in the 1980s, and later appropriated by the former Institute for Economic, Social and Environmental Development of the State of Pará (Idesp) in the 1990s, which became the main organ responsible for the creation of the unit; most of the respondents are unaware of APA Combu Island, only a small parcel of the respondents was informed /consulted about the creation process of the APA; this query was performed in an informal way. It is assumed that, in sustainable use conservation units, the participation of the resident population is essential for a successful planning and management, although the managing agency does not have many resources to be used in the administration. From the analysis of all these data together, we concluded that the creation process of the APA Combu Island is the main obstacle to consolidate the unit management, since it happened so apart from the knowledge of the resident population.